The role of culture and society in the development of plot in tanushree podders escape from harem and gita mehtas a river sutra: a feminist reading - Khandhar, Diren Ashok; Mani, Manimangai (SciPress, 2015)
Culture and Society are often the main gist of most novels. These two factors often influence and control the characters, thus helping in the development of the plot. A plot, as defined by Egan (1978), is used to indicate an outline of events and serves as a skeleton in a literary piece. In other words, it is a tool in making sure the main incidents or scenarios are presented in a particular order to establish a clear understanding of what is being written. Culture and society plays the essence in a novel as it constructs these main ideas in engaging the interest of a reader and also extends the intended message of the particular writer. This paper looks into how culture and society helps in developing the plots of the selected novels using the feminist approach. Tanushree Podder’s, Escape from Harem (2013) and Gita Mehta’s A River Sutra (1993) amazingly are both set in India. Podder and Mehta have inserted the perception society had over women and how male supremacy was glorified in many aspects. The essence of feminist approach was very much present in these two novels. According to Tyson (2006), feminism concerns the ways in which literature undermines the economic, political, social and psychological oppression on women. Though the setting of both novels fall in different eras but the theme of female oppression remains the same. The patriarchal society uses culture and religion as a tool to control women and oppress them. Both authors have shown how the women in the 17th century and in the 20th century face the same kind of judgment from the society and men in general.